PENGARUH JUMLAH BUS SIAP OPERASI DENGAN JUMLAH PENUMPANG DIANGKUT PADA PT. JAKARTA MEGA TRANS - PAYAMAN MANIK; INDRA SUWARLAN (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
PT. Jakarta Mega Trans (PT. JMT) is a TransJakarta bus operator and formed of four transport companies consortium which are PT. Mayasari Bakti, PT. Steady Safe, Perum PPD, and PT. BPW Pahala Kencana. This study is aimed to find out and understand the relationship between the operated buses and the carried passengers. The method of the study is Spearman Rank correlation analysis and hypothesis test. Based on the result and analysis, there is a significant relationship between the operated buses and carried passengers which is ρ = 0.7824. The hypothesis test shown that ρhitung > ρtabel (0.7824 > 0.777) which support the previous result.